Transforming informal work and livelihoods in Costa Rica and Nicaragua - Enrique Alaniz; Thomas Gindling; Catherine Mata; Diego Rojas (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
We divide workers into six work statuses: formal self-employed, upper-tier informal self-employed, lower-tier informal self-employed, formal wage-employed, upper-tier informal wage-employed, and lower-tier informal wage-employed. In both Costa Rica and Nicaragua, earnings are highest for formal work, next for upper-tier informal, and last for lower-tier informal. Mobility out of lower-tier informal work is higher than out of all other work statuses. While many lower-tier informal workers leave employment or transition into other informal statuses, most transitions are from lower-tier informal into upper-tier informal and formal work. Transitions from all types of informality into formality are more common in Costa Rica than in Nicaragua, partly due to the larger proportion of formal workers within Costa Rica (58 per cent vs 19 per cent). Regressions of transitions on worker characteristics suggest that policies of providing vocational training and formal education to informal workers can promote transitions into betterpaying work statuses.
Keywords: J62; J63; O17; O54; 330; employment; informal; worker mobility; Costa Rica; Nicaragua